El sindicalismo español en perspectiva europea: de la anomalía a la convergencia - Beneyto, Pere J. (Cuadernos de Relaciones Laborales, 2008)
In the context of European unionism, the Spanish case has been traditionally considered as quite singular, both because of its late legalisation and for its structural weakness. Nevertheless, in the latest years, it has developed an important process of renewal of its organisation and strategies, which has lead to a sustained growth of its memberships and representativeness at the extent of approaching the average level among European countries in some key variables, as shown by recent surveys and compared studies. Upon the basis of recent empirical information, the paper examines the key factors that explain unionism in Spain and Europe, with special attention to membership and representativeness. In examining other comparative data of time and national contexts, we conclude suggesting the existence of a process of convergence between the Spanish case and the European evolution